2021
DOI: 10.1016/j.ekir.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir in Patients With Estimated GFR <30 ml/min per 1.73 m2 or on Renal Replacement Therapy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…Estiverne et al reported a case series on 18 patients with CrCl<30 ml/min/1.73m 2 or on renal replacement therapy that received remdesivir. Mean CRP and d dimer levels were 133.1 mg/dl and 2196 ng/ml, comparative to our results [13]. 35% of the patients in our study died, slightly higher than prior studies that showed mortality rates of 26-32% [14, 15].…”
Section: Discussioncontrasting
confidence: 63%
“…Estiverne et al reported a case series on 18 patients with CrCl<30 ml/min/1.73m 2 or on renal replacement therapy that received remdesivir. Mean CRP and d dimer levels were 133.1 mg/dl and 2196 ng/ml, comparative to our results [13]. 35% of the patients in our study died, slightly higher than prior studies that showed mortality rates of 26-32% [14, 15].…”
Section: Discussioncontrasting
confidence: 63%
“…Pettit et al found no significant increase in adverse events, nor increases in ALT, AST or serum creatinine when remdesivir was given to patients with eGFR < 30mL/min/1.73m 2 compared to patients with eGFR > 30mL/min/.73m 2 , and that none of the transaminase or creatinine elevations were attributed to remdesivir use [27]. Estiverne et al found that among 18 patients with eGFR < 30mL/min/1.73m 2 who received remdesivir, there were 2 cases of transaminitis (ALT or AST > 5 times the upper limit of normal), both of which were attributed to shock liver [30]. Aiswarya et al…”
Section: Discussionmentioning
confidence: 99%
“…39 However, multiple small case series have suggested remdesivir may be safe in patients with eGFR < 30 mL/min/1,73m 2 or on dialysis. [40][41][42] A post hoc analysis of clinical trial data showed that patients treated with remdesivir had less kidney function decline; 30% of patients receiving placebo experienced a decline in creatinine clearance, whereas only 15% of patients on a 5-day remdesivir course experienced a decline in creatinine clearance. 43 Studies summarizing the inclusion and exclusion criteria of clinical trials of therapeutics for COVID-19 have noted that kidney disease is an exclusion criteria in approximately half of trials.…”
Section: Acute Chronic and End-stage Kidney Disease As Risk Factors For Mortality From Covid-19mentioning
confidence: 99%